PENGEMBANGAN MEDIA PEMBELAJARAN TRAINER PENGENDALIAN MOTOR LISTRIK 3 PHASE BERBASIS SMART RELAY ZELIO PADA MATA PELAJARAN INSTALASI MOTOR LISTRIK DI SMK NEGERI 1 SUSUT - I Kadek Putra Sanjaya; Nyoman Santiyadnya; I Putu Suka Arsa (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This study aims to create a three-phase electric motor control trainer based on smart relay zelio, to determine the feasibility and students’ response toward the learning media of a three-phase electric motor control trainer based on smart relay zelio on Electrical Motor Installation’s subject in Electrical Power Installation Engineering Department of SMK Negeri 1 Susut. This study used Research and Development (R&D) Method. In collecting the data, this study used a questionnaire that was assessed by content experts, media experts, and students of SMK Negeri 1 Susut. The result of the study obtained the result of the validity test from the content experts showed a percentage of 93,75 % categorized as very decent qualification, the result of the validity test from media experts showed the percentage of 97,73% categorized as very decent qualification, the result of the validity test from the small group which consisted of 5 respondents showed that all of them were categorized as excellent, and the results of the large group with 12 respondents showed that all in the excellent category. Based on the result of the study, the learning media of the 3-phaseectric motor control trainer based on smart relay zelio is suitable to apply in the process of Electrical Motor Installation.